Modeling of geochemical processes in the submarine discharge zone of hydrothermal solutions - Sudarikov Segrei M. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Санкт-Петербургский горный университет», 2017)
The paper reviews the main methods and analyzes modeling results for geochemical processes in the submarine discharge zone of hydrothermal solutions of mid-ocean ridges. Initial data for modeling have been obtained during several marine expeditions, including Russian-French expedition SERPENTINE on the research vessel «Pourquoi Рas?» (2007). Results of field observations, laboratory experiments and theoretical developments are supported by the analysis of regression model of mixing between hydrothermal solutions and sea water. Verification of the model has been carried out and the quality of chemical analysis has been assessed; degree and character of participation of solution components in the hydrothermal process have been defined; the content of end members has been calculated basing on reverse forecasting of element concentration, depending on regression character; data for thermodynamic modeling have been prepared. Regression model of acid-base properties and chloridity of mineralizing thermal springs confirms adequacy of the model of double-diffusive convection for forming the composition of hydrothermal solutions. Differentiation of solutions according to concentrations of chloride-ion, depending on temperature and pH indicator within this model, is associated with phase conversions and mixing of fluids from two convection cells, one of which is a zone of brine circulation. In order to carry out computer thermodynamic modeling, hydro-geochemical and physicochemical models of hydrothermal discharge zone have been created. Verification of the model has been carried out basing on changes of Mn concentration in the hydrothermal plume. Prevailing forms of Mn migration in the plume are Mn2+, MnCl+, MnCl2. Two zones have been identified in the geochemical structure of the plume: 1) high-temperature zone (350-100 С) with prevalence of chloride complexes – ascending plume; 2) lowtemperature zone (100-2 С), where predominant form of transfer is a free divalent ion – lateral plume. Sulfate complex in insignificant quantities (1.5 %) is detected in the lateral plume, whereas hydroxide complex is stable at temperatures 325-125 С and can only be found in the ascending plume. Results of modeling almost fully correspond to field observations. Verification of thermodynamic model proves its adequacy and allows to make a transition to the next stage of research – examination of geochemical dissipation for key ore components of hydrothermal solutions – Fe, Cu, Zn etc.
Keywords: mid-ocean ridge; regression model; thermodynamic modeling; hydrothermal solution; migration forms